Combination of symptoms, syndrome and disease: Treatment of refractory diabetic gastroparesis - Li, Jun-Ling (Baishideng Publishing Group Inc, 2014)
AIM: To assess effect of combination of symptoms, syndrome and disease on treatment of diabetic gastroparesis with severe nausea and vomiting. METHODS: Professor Tong Xiaolin’s clinical electronic medical records of patients who were treated between January 1, 2006 and October 1, 2012 were used as a database. Patients who met the inclusion criteria were enrolled. General information (name, sex and age), symptoms and blood glucose levels were obtained from the clinic electronic medical record, which was supplemented by a telephone interview. The patient-rated Gastroparesis Cardinal Symptom Index (GCSI) was used to evaluate the severity of the symptoms of gastroparesis. The effects of the treatment were assessed by the change in the severity of the symptoms of gastroparesis and the change in blood glucose between the baseline levels and the post-treatment levels at 1, 2, 4, 8 and 12 wk. RESULTS: Forty-five patients had a mean GCSI nausea and vomiting severity score of 4.21 ± 0.67 and a total GCSI score of 2.77 ± 0.63 before treatment. There was a significant improvement in the nausea and vomiting score at every return visit compared with the baseline score (1 wk: 3.02 ± 1.04 vs 4.18 ± 0.71, P < 0.001; 2 wk: 2.32 ± 1.25 vs 4.16 ± 0.73, P < 0.001; 4 wk: 2.12 ± 1.26 vs 4.12 ± 0.73, P < 0.001; 8 wk: 1.79 ± 1.09 vs 4.24 ± 0.77, P < 0.001; 12 wk: 0.69 ± 0.92 vs 4.25 ± 0.70, P < 0.001). Twenty-five of the 45 patients had complete resolution of vomiting during the observation period (mean time to resolution was 37.9 ± 27.3 d). The postprandial fullness and early satiety subscale, bloating subscale and total GCSI scores were also improved. Finally, the blood glucose levels improved after treatment, although the change was not significant. CONCLUSION: Use of the combination of symptoms, syndrome and disease to treat diabetic gastroparesis with refractory nausea and vomiting may be a new treatment option.